2021
DOI: 10.1021/acs.iecr.1c02261
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Bed Adsorption of CO2, CH4, and N2 and Their Mixtures in Potassium-Exchanged Binder-Free Beads of Y Zeolite

Abstract: The adsorption of carbon dioxide (CO 2 ), methane (CH 4 ), and nitrogen (N 2 ) has been studied on potassium-exchanged (95%) binder-free beads of Y zeolite through single, binary, and ternary fixed bed breakthrough experiments, covering the temperature range between 313 and 423 K and a pressure of up to 350 kPa. At 313 K and 350 kPa, the single-component data obtained showed that the amounts adsorbed of CO 2 , CH 4 , and N 2 are around 6.42, 1.45, and 0.671 mol kg −1 , respectively. The binary experiments CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Micropore (intracrystalline) or macropore diffusion (intercrystalline) may control the mass transfer mechanism within adsorbent particles. Previous research has revealed that adsorption on the zeolites was controlled by both macropore- and micropore-diffusion mechanisms. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micropore (intracrystalline) or macropore diffusion (intercrystalline) may control the mass transfer mechanism within adsorbent particles. Previous research has revealed that adsorption on the zeolites was controlled by both macropore- and micropore-diffusion mechanisms. , …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has revealed that adsorption on the zeolites was controlled by both macroporeand micropore-diffusion mechanisms. 33,34 This way, gravimetric and volumetric techniques have mainly been used for gas storage and separation studies. Gravimetric techniques have some shortcomings, such as considering the buoyancy effect on the volume of the system, the incapability of investigating multicomponent adsorption, and the high cost of the unit.…”
Section: Introductionmentioning
confidence: 99%
“…However, under industrially relevant conditions, the CO 2 separation using physical adsorbents such as zeolites is performed in a fixed bed configuration under dynamic conditions where the separation performance of adsorbents is dictated by the capacity, selectivity, and cyclability. Hence, despite being scarcely reported for novel laboratory-scale adsorbents, breakthrough measurements are mandatory to properly understand and evaluate the practical application of zeolitic adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption processes are widely acknowledged as economically efficient and appealing alternatives for addressing various industrial challenges, including but not limited to postcombustion CO 2 capture, H 2 purification from steam methane reforming (SMR), medical O 2 concentrator, biogas upgrading, and separation of straight-chain hydrocarbons from the branched chain. Consequently, pressure swing adsorption (PSA), which is a cyclic process that uses pressure driven to perform bulk separation, is commonly used for H 2 purification from SMR. , The typical SMR off-gas is a mixture of H 2 /CH 4 /CO/CO 2 with a composition of 76/3/4/17%, respectively. From this composition, the conventional PSA can achieve purities of up to 99.9999% with high recoveries of around 96% .…”
Section: Introductionmentioning
confidence: 99%